Implementation of Kanban System in Manufacturing Process - Sharma, Prabal; Sahu, Rinkey (International Journal of Scientific Research in Civil Engineering, 2020)
A successful implementation of kanban system have been done in the production system, in search of the ideal results of it, whole setup was done at a leading TMT manufacturing unit, A pull nature of kanban have been established and then the data is collected first, before that proper training is given to the workers of the organization, and keeping in mind all the necessary before implementation like 5s just in time and lean manufacturing concepts, after that 3 sets of data has been taken after the implementation of the kanban process, taking all the factors viz replenishment factor, buffer stock etc after that calculation has done and the optimum results have been achieved, the required results are then compared with the old data which was taken before the implementation of kanban, Results have been bifurcated in terms of Time , increase in Production and Increase in profit as well as cost savings.